Klasifikasi Dokumen E-Complaint Kampus menggunakan BM25 dan K-Nearest Neighbor - Khairinnisa Rifna; Imam Cholissodin; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
In an educational institution, a forum is absolutely needed where the academic community severely provides suggestions and criticisms about what they feel about the educational institution facilities such as a forum for criticism and suggestions provided by Brawijaya University, namely e-complaint. E-complaint is a facility managed by the campus as a means of accommodating suggestions, criticisms, opinions from users regarding services or facilities provided by the campus. However, the e-complaint facility is currently considered to be less than optimal because the criticism or suggestions submitted by the academic community are not processed quickly by the parties concerned. This is because the e-complaint manager sorts the documents manually which causes a long time process and the e-complaint manager does not sort the documents based on importance and urgency so that the process of solving the e-complaint's problem is not sorted by the priority of the urgency. Therefore, a system is needed that can classify campus e-complaint documents based on their level of importance and urgency. In this study, a text pre-processing process was carried out, which was then carried out using the BM25 method as a ranking method and the K-Nearest Neighbor method as a classification method. Based on the test results using k-fold cross validation, the highest average value of precision is 1, recall value is 0,46875, f-measure value is 0,6875.